Multiple faces of preferential market access: their causes and consequences. Issue 73 (11th February 2013) - Egger, Peter; Wamser, Georg
Summary This paper suggests an integrated approach to study selection into and consequences of five modes of preferential economic integration agreements (PEIAs): goods trade agreements (GTAs), services trade agreements (STAs), double taxation treaties (DTTs), bilateral investment treaties (BITs), and currency unions as well as currency pegs (CUAs). A detailed descriptive analysis reveals typical integration patterns, with DTTs and BITs often being first steps towards deeper integration. We consider the effects of PEIAs on bilateral goods trade, services trade, and FDI and provide conclusive evidence that single and combined PEIAs are associated with positive effects not only on single outcome but typically on all outcomes. Investment liberalization through DTTs and BITs seems to be particularly beneficial since concluding them alone or in any combination with other agreements encourages goods trade even more than the liberalization of goods trade per se. — Peter Egger and Georg Wamser